BOROBUDUR TEMPLE PRE AND POST COLONIAL ERA - Baskoro Suryo Banindro (DeKaVe, 2015)
Borobudur temple is a heritage of Buddhism culture in Indonesia, which located at Magelang city, Central Java Province. The temple was built at the golden era of Syailendra dynasty, built among 800 AD or around 9th century. Beside known as one of Indonesia’s main tourism destination, it is also a central of Buddhism spiritual religion liturgies and rituals. Borobudur ever was in a tremendous golden era but also the darkness was covered its existence until hundred of years and it’s began to be revealed in the era of colonial. For decades, the rejuvenation and revitalization effort to rebuild the temple back to the original shape been accomplished. Through serious treatments, Borobudur becoming the inspiration source of cultural activities of various aspect that manifested, mainly history, arts, tourism, economy, research, science and also religion. The walls of Borobudur are full of reliefs that picture the Buddhism philosophy, and turn out to be a masterpiece with a high aesthetic in the accession of civilization in its era. Now, beside stated as one of the World Heritages by UNESCO, also 2 titles given to the temple; as the archeology site heritages, the biggest Buddhism temple in the world, and also recorded in Guinness World Records.